Intractable hypercalcaemia during pregnancy and the postpartum secondary to pathogenic variants in CYP24A1. (21st November 2019) - Arnold, Nirusha; O'Toole, Victor; Huynh, Tien; Smith, Howard C; Luxford, Catherine; Clifton-Bligh, Roderick; Eastman, Creswell J
Abstract : Summary: Parathyroid-independent hypercalcaemia of pregnancy, due to biallelic loss of function of the P450 enzyme CYP24A1, the principal inactivator of 1, 25(OH)2 D results in hypervitaminosis D, hypercalcaemia and hypercalciuria. We report two cases of this disorder, with intractable hypercalcaemia, one occurring during gestation and into the postpartum, and the other in the postpartum period. Case 1, a 47-year-old woman with a twin pregnancy conceived by embryo transfer, presented with hypercalcaemia at 23 weeks gestation with subnormal serum parathyroid hormone (PTH) and normal serum 25-OH D levels. She was admitted to hospital at 31 weeks gestation with pregnancy-induced hypertension, gestational diabetes and increasing hypercalcaemia. Caesarean section at 34 weeks gestation delivered two healthy females weighing 2.13 kg and 2.51 kg. At delivery, the patient's serum calcium level was 2.90 mmol/L. Postpartum severe hypercalcaemia was treated successfully with Denosumab 60 mg SCI, given on two occasions. CYP24A1 testing revealed she was compound heterozygous for pathogenic variants c.427_429delGAA, (p.Glu143del) and c.1186C>T, (p.Arg396Trp). Case 2, a 36-year-old woman presented 4 days after the delivery of healthy twins with dyspnoea, bradycardia, severe headaches, hypertension and generalized tonic-clonic seizures after an uneventful pregnancy. She was hypercalcaemic with a suppressed PTH, normal 25(OH)D, and elevated 1, 25(OH)2 D levels. Her symptoms partially responded to i.v. saline and corticosteroids in the short term but bisphosphonates such as Pamidronate and Zoledronic acid did not result in sustained improvement. Denosumab 120 mg SCI successfully treated the hypercalcaemia which resolved completely 2 months post-partum. CYP24A1 testing revealed she was homozygous for the pathogenic variant c.427_429delGAA, (p.Glu143del). Learning points: Hypercalcaemia in pregnancy can be associated with considerable morbidity with few options available for management. In non-PTH-related hypercalcaemia the diagnosis of CYP24A1 deficiency should be considered. Making a definitive diagnosis of CYP24A1 deficiency by genetic testing delays the diagnosis, while the availability of serum 24, 25-dihydroxyvitamin D (24, 25(OH)2 D) will expedite a diagnosis. In pregnant women with CYP24A1 deficiency hypercalcaemia can worsen in the post-partum period and is more likely to occur with twin pregnancies but generally resolves within 2–3 months. Therapeutic alternatives are limited in pregnancy and their effectiveness is short-lived and mostly ineffective. Denosumab used in both our patients after delivery was the most effective agent normalizing calcium and may have benefit as a long-term therapeutic agent in preventing complications in patients with CYP24A1 deficiency.